Light-Induced Dynamic Change of Phytochrome B and Cryptochrome 1 Stabilizes SINATs in Arabidopsis - Hu, Jin; Hu, Yinmeng; Yang, Mengran; Hu, Xiaotong; Wang, Xuelu (Frontiers in Plant Science, 2021)
Ubiquitin-dependent protein degradation plays an important role in many plant developmental processes. We previously identified a class of SINA RING-type E3 ligases of Arabidopsis thaliana (SINATs), whose protein levels decrease in the dark and increase in red and blue light, but the underlying mechanism is unclear. In this study, we created transgenic lines carrying point mutations in SINAT genes and photoreceptors-NLS or -NES transgenic plants to investigate the regulatory mechanism of SINAT protein stability. We demonstrated that the degradation of SINATs is self-regulated, and SINATs interact with photoreceptors phytochrome B (phyB) and cryptochrome1 (CRY1) in the cytoplasm, which leads to the degradation of SINATs in the dark. Furthermore, we observed that the red light-induced subcellular localization change of phyB and blue light-induced the dissociation of CRY1 from SINATs and was the major determinant for the light-promoted SINATs accumulation. Our findings provide a novel mechanism of how the stability and degradation of the E3 ligase SINATs are regulated by an association and dissociation mechanism through the red light-induced subcellular movement of phyB and the blue light-induced dissociation of CRY1 from SINATs.